Inheritance of seed yield, maturity and seed weight of common bean (Phaseolus vulgaris) under semi-arid rainfed conditions - White, Jeffrey W.; Ochoa Marquez, R; Ibarra Perez, FJ; Singh, Shree P. (Cambridge University Press, 1994)
To develop an effective breeding programme for rainfed production of the common bean (Phaseolus vulgaris L.), the inheritance of seed yield under such conditions should be understood, preferably considering the effects of environment to account for site or season specificity. Thus, heritability, expected and realized gain from selection, and combining ability were evaluated for a nine-parent diallel of common bean without reciprocals but including parents, at two locations each in Mexico and Colombia, using the F2 and F3 population bulks. Heritability estimated from regressions of F3 on F2 ranged from 0·09 ± 0·18 (S.E.) to 0·75±0·25 for seed yield, from 0·26±009 to 0·34±009 for days to maturity and from0·57±004 to 0·80±004 for 100-seed weight. Expected gain from selection in the F2 was estimated as a percentage of the population mean, selecting the upper 20% of the populations. Expected gain in seed yield ranged from 1·8 to 8·4% in Mexico and from 6·5 to 28·1% in Colombia. Realized gains in seed yield in the F3 were 0·4–7·4% in Mexico and 2·9–15·7% in Colombia. Realized gain values for days to maturity were < 2·2%, and for 100-seed weight > 13·4%. General combining ability (GCA) mean squares (estimated using Griffing's Method 2, Model 1) were significant (P <0·01) and larger than those for specific combining ability (SCA) for all traits at all locations. The parents from the Mexican highlands tended to have a positive GCA effect for yield in Mexico but negative values in Colombia, whereas parents adapted to mid-elevation tropical environments showed the opposite tendency. However, all significant GCA values of breeding line V8025 were positive in both countries.